Familial Xq27.1q28 duplication arising from a maternal interarm forward insertion of the X chromosome: a case report - Li, Xiang; Peng, Yuan-Mei; Luo, Bo-Wen; Luo, Yu-Di; Qin, Yun-Rong; Feng, Keng; Li, De-Rong; Yang, Zeng-Yu; Zhu, Ling-Ling; Pan, Jin-Jie; Song, Ju-Jie; Liang, Jian; et al. (Frontiers in Genetics, 2025)
ObjectiveThis study investigates a rare case of Xq27.1q28 duplication arising from a maternal interarm forward insertion of the X chromosome, focusing on prenatal diagnosis, family analysis, and genetic counseling for a pregnant woman with repeated adverse pregnancy outcomes.MethodsConducted in March 2023 at Yulin Maternal and Child Health Hospital, blood samples from the proband’s mother, her husband, and her family, along with umbilical cord blood from the proband. G-banding chromosomal karyotyping and CNV-seq were performed and interpreted according to ACMG guidelines. The aim was to trace the origin of genetic variations and assess recurrence risks.ResultsThe grandmother had a 46,X,ins(X) (p22.1q27q28) karyotype; the proband’s mother had a 46,X,rec(X)dup (Xq)ins(X) (p22.1q27q28)dmat karyotype; and the proband had a 46,Y,rec(X)dup (Xq)ins(X) (p22.1q27q28)mat karyotype. This indicated the proband’s chromosome was inherited from the mother, originating from the grandmother. Other family members had normal karyotypes. NGS revealed a pathogenic 15.65 Mb duplication in the Xq27.1-q28 region, which was present in the proband and his mother, confirming the maternal X-chromosome insertion as the cause of the duplication.ConclusionThe grandmother’s chromosomal insertion in the Xq27.1q28 duplication in both the proband’s mother and her offspring. Given the X-linked dominant inheritance pattern, there’s a 50% recurrence risk in future offspring. Genetic counseling emphasized the importance of assisted reproductive technology (ART) for future pregnancies to mitigate the risk of recurrence.